Intimate partner violence and family planning practices in selected South Asian countries / Hoo Keh Yoong - Hoo , Keh Yoong (2024)
Intimate partner violence (IPV) and family planning (FP) practices are critical public health concerns in the less developed regions, including South Asia, yet their interconnection remains underexplored. Collaborative efforts between governments and international bodies have aimed to promote FP, but universal access to contraception and addressing unmet needs remains a challenge in many less developed countries. This study focuses on IPV prevalence, contraceptive use, and unmet need for FP in four South Asian countries: Afghanistan, India, Nepal, and Pakistan. Specifically, this study aims to 1) investigate the prevalence of IPV, contraceptive use, and unmet need for FP across South Asian countries; 2) examine the association of IPV and socio-economic variables with contraceptive use in South Asian countries; 3) examine the association of IPV and socio-economic variables with unmet need for FP in South Asian countries. Using data from the Demographic and Health Surveys (DHS), this study concentrates on married women aged 15-49 who responded to the domestic violence module. Crosstabulations and Fisher’s exact tests/chi-square tests were used to examine the bivariate relationships, while multinomial logistic regression was employed to analyze the net effect of each independent variable on FP practices. Eight regression models explore the impact of different IPV types (physical, sexual, emotional, and combined types of IPV) on FP practices. Findings indicate that physical violence is predominant in Afghanistan, India, and Nepal, while emotional violence is more prevalent in Pakistan. Across the countries, Afghanistan had the highest prevalence rate of all forms of violence, as well as controlling behaviors by husbands. India had the highest contraceptive prevalence rate (CPR) of any modern contraceptive method, while Afghanistan had the lowest modern CPR. The multivariate analysis reveals that the relationship between IPV and FP practices varies across South Asian countries. In Afghanistan, women who experienced any form of violence and husbands’ controlling behaviors were more likely to use modern contraceptive methods. However, in India, women who experienced sexual violence and husbands’ controlling behaviors were less likely to use modern contraceptive methods. Conversely, Indian women who experienced emotional violence and husbands’ controlling behaviors and Pakistani women who experienced physical and emotional violence have a higher unmet need for spacing. Similarly, Indian women who experienced sexual violence have a higher unmet need for limiting. However, Afghan women have lower unmet need for spacing and limiting among those who experienced physical and emotional violence. Additionally, the study identifies several key predictors of FP practices, including women's education, employment, household wealth, and exposure to FP messages through media. Generally, women who were educated, employed, from wealthy family, and had FP exposure were more likely to use modern contraceptive methods and less likely to have unmet need for FP. Notably, in Afghanistan, women with higher education and from wealthier backgrounds exhibit poorer FP practices compared to their lesser educated and poorer counterparts in other countries, especially India. The study emphasizes the importance of initiatives that enhance women's education, create employment opportunities, boost empowerment, and confront deep-seated cultural barriers to address IPV and unmet need for FP in South Asia.